MOLECULAR PHYLOGENY OF GALL-FORMING APHIDS TRIBE FORDINI (HOMOPTERA, APHIDIDAE, ERIOSOMATINAE) ON PISTACIA TREES FROM KURDISTAN REGION NORTH OF IRAQ - & et al., Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Four aphid species belonging to the Tribe Fordini (Homoptera, Aphididae, Eriosomatinae) induce galls on Pistacia trees in North Iraq (Kurdistan) were recorded in this study. Molecular phylogeny of Iraq Fordini species was constructed for These species (Forda riccobonii, Paracletus cimiciformis, Baizongia pistaciae and Forda marginata), based on sequences of mitochondrial Cytochrome Oxidase I (COI) gene of these aphid species to detect the relationship and taxonomy of Iraqi species for tribe Fordini. Our results confirmed that each of Forda and Paracletus are a sister genus, or monophyletic group by designing in same clade, while B. pistaciae is separate from other clades, supporting the taxonomic division of the tribe Fordini into two subtribes (Fordina and Baizongina).